The Effect of Mastering Pedagogical Competence on the Prospective Elementary School Teachers Teaching Readiness - Muhammad Shabir Umar; Muljono Damopolii; Fitriani Nur; Suharti Suharti (UIN Siber Syekh Nurjati Cirebon, 2021)
AbstractThis study aims to determine the description of mastering pedagogical competence, map the teaching readiness, and analyze the significant effect of mastering pedagogical competence on teaching readiness of the prospective elementary school teachers at State Islamic University (UIN) Alauddin Makassar, Indonesia. This research was ex-post-facto quantitative research. The research variables were pedagogical competence and the readiness to be a teacher. The population and sample were all of the final semester students, consisting of 80 students of Madrasah Ibtidaiyah Teacher Education Department at UIN Alauddin Makassar who had taken the Field Experience Practice program using simple random sampling. The instrument used was a Likert scale-based questionnaire. A basic linear regression was employed to analyze the data. The following are the results of this study: (1) the mean score of prospective elementary school teachers' pedagogical competence was 70.62, indicating that the pedagogical competency score was in the high category; (2) the mean score of prospective elementary school teachers' teaching readiness mapping was 72.25, indicating that the mapping score of teaching readiness was in the high category; (3) the mean score of prospective elementary school teachers' pedagogical competence was 70.62, indicating that the pedagogical competency score was in the high category. Â As a result, prospective elementary school teachers' teaching preparation was influenced by their knowledge of pedagogical competence. Accordingly, prospective elementary school teachers' teaching preparation is needed to be trained by developing pedagogical competency by constructing a learning program in the Madrasah Ibtidaiyah Teacher Education Department.Keywords: pedagogical competence, teaching readiness, prospective elementary school teachers.AbstrakPenelitian ini bertujuan untuk mendeskripsikan penguasaan kompetensi pedagogik, memetakan realitas kesiapan mengajar, dan mengetahui signifikansi pengaruh penguasaan kompetensi pedagogik terhadap kesiapan mengajar calon guru sekolah dasar di Universitas Islam Negeri (UIN) Alauddin Makassar, Indonesia. Penelitian ini adalah penelitian kuantitatif jenis ex-post facto. Variabel penelitian yaitu kompetensi pedagogik dan kesiapan menjadi guru. Populasi dan sampel yaitu seluruh mahasiswa semester akhir program studi Pendidikan Guru Madrasah Ibtidaiyah (PGMI) UIN Alauddin Makassar yang telah mengambil program praktik pengenalan lapangan (PPL), dengan sampel random sampling sejumlah 80 orang. Instrumen yang digunakan yaitu angket berbasis skala Likert. Teknik analisis data yang digunakan adalah regresi linear sederhana. Berdasarkan penelitian yang telah dilakukan, diperoleh bahwa: (1) rata-rata skor kompetensi pedagogik calon guru sekolah dasar adalah 70.62 yang berarti secara umum skor kompetensi pedagogik berada pada kategori tinggi, (2) rata-rata pemetaan kesiapan mengajar calon guru sekolah dasar adalah 72.25 yang berarti skor pemetaan kesiapan mengajar berada pada kategori tinggi, dan (3) terdapat pengaruh yang signifikan kompetensi pedagogik terhadap kesiapan mengajar calon guru sekolah dasar. Sehingga dapat disimpulkan bahwa penguasaan kompetensi pedagogik mempengaruhi kesiapan mengajar calon guru sekolah dasar. Oleh karena itu, kesiapan mengajar calon guru sekolah dasar perlu dipersiapkan secara matang melalui penguatan kompentesi pedagogik baik melalui penyiapan kurikulum pembelajaran pada jurusan Pendidikan Guru Madrasah Ibtidaiyah.Kata kunci: kompetensi pedagogik, kesiapan mengajar, calon guru sekolah dasar.